Uncertainty in information systems : an introduction to techniques and applications - Hunter, Anthony, 1962- (London ; New York : McGraw-Hill Pub. Co., 1996)
This text is intended to highlight the significance of uncertainty in the management of information, introduce methods of modelling uncertain information and discuss current and potential applications of such methods in information systems.
Includes bibliographical references (p. 165-184) and index.
oif 16/02/15
Loan
Keywords: Database management; Uncertainty (Information theory); Information technology